STUNTING, PEMERIKSAAN KEHAMILAN DAN KONSUMSI TABLET TAMBAH DARAH IBU HAMIL DI INDONESIA: ANALISIS DATA RISKESDAS 2013 - Nina Fentiana; Formaida Tambunan; Daniel Ginting (STIKES Suaka Insan, 2022)
The stunting rate of children under the age of two in Indonesia increased by 3.8% from the year of 2016 to 2018. Stunting in children, besides having an impact on children's growth and development, also results in economic losses because physical growth failure reduces productivity. Cognitive failure causes decreased performance in school, so that increase health care costs. The purpose of the study was to determine the relationship between pregnancy check-ups and the consumption of blood-supplemented tablets (TTD) in pregnant women with stunting ? 90 tablets in Indonesia by analyzing the 2013’ Riskesdas data. The final analytical sample was 11,029 aged 0-2 years in all provinces in Indonesia. Statistical analysis was performed with chi-square at a significance level of 5%. Stunting children 0-23 months in Indonesia is 33.3%. Chi-square analysis showed that there was a relationship between standardized antenatal care and consumption of TTD in pregnant women 90 tablets with stunting in children aged 0-23 months (p<0.05). Mothers who do not carry out standardized pregnancy check-ups have a 1.03 times risk of having stunting children compared to mothers who carry out standardized antenatal care. Mothers who took TTD <90 tablets had a 1.05 times chance of having stunting children compared to mothers who took TTD 90 tablets. Keywords: Antenatalcare, Children under two years; Stunting; consumption of iron tablets